Incidence of tax culture on the recovery of the general sales tax in nongovernmental organizations in Peru - Mamani Mamani, Raul (2022)
Objective: To determine the incidence of tax culture in the management of General Sales Tax (IGV) recovery in Non-Governmental Organizations (NGOs) of social projection in Peru registered with the Peruvian Agency for International Cooperation (APCI). Method: The research was qualitative in approach, descriptive in scope and non-experimental in design; information was obtained from 1,502 Peruvian NGOs registered with the APCI. The technique used was a documentary review to obtain statistical information on the recovery of the IGV from the APCI database, as well as an in-depth interview to describe the perception of the level of tax culture in the NGOs. Moreover, the information was put in statistical tables and subsequently subjected to analysis and interpretation. Results: It was observed that NGOs with an ideal framework of 18% of IGV recovery, on average, only recovered 8.39% in the last 5 years, failing to receive 9.61% due to the absence of tax management. Conclusion: Tax culture plays a determining role in the recovery of the IGV of the NGOs registered in the APCI, which allows to continue with the sustainability of social projects in Peru.